The effect of adding curcuma extract (Curcuma zanthorrhiza) to commercial feed on the growth and survival of carp fry (Cyprinus carpio) - Siti Arfah; Siti Komariyah; Suri Purnama Febri; Shadiqa Malahayati (Acta Aquatica: Aquatic Sciences Journal, 2026)
Carp (Cyprinus carpio) is one of the freshwater fish species with high economic value and is widely cultivated due to its high adaptability to environmental conditions, ease of breeding, and rapid growth. This study aims to analyze the effect of adding turmeric extract to commercial feed on the growth and survival of carp fry and to determine the optimal dose of turmeric extract for the growth and survival of carp fry. The study was conducted in March 2024 over 40 days at the Hatchery Laboratory of the Aquaculture Program, Faculty of Agriculture, Samudra University. The curcuma extract was prepared at the Chemistry Laboratory of Syiah Kuala University. The research method used was a Completely Randomized Design (CRD) with 4 treatments and 3 replications. Where P1 (without curcuma extract administration), P2 (curcuma extract administration at 10 ml/kg of feed), P3 (curcuma extract administration at 20 ml/kg of feed), and P4 (curcuma extract administration at 30 ml/kg of feed). The research results showed that the best feed intake was in P4 (76.50 g), the best absolute length growth was in P4 (4.58 cm), and the best absolute weight growth was in P4 (3.64 g). the best daily growth rate was in P4 (3.15%), the best survival rate was in P4 (90%), and the lowest feed conversion ratio was in P4 (2.18%). Keywords: Carp (Cyprinus carpio); Curcuma Extract; Growth Survival Rate